Efektifitas Pembalikan Beban Pembuktian dalam Tindak Pidana Gratifikasi (Lex Jurnalica, 2010)
The criminal act gratuity provided for in article 12 paragraph B (1) letter a reversal of the burden of proof be the basis, but in the formulation of the core offense listed in full implications of mandatory prosecution to prove the offense formulation. This study aims to determine whether the reversal of the burden of proof is the obligation or right of the receiving gratuities. In addition, research was done in order to determine the effectiveness of the application of Article gratification of article 12 paragraph B (1) letter a of Law Number 20 Year 2001 regarding Amendment to Law Number 31 Year 1999 on Eradication of Corruption Criminal Acts. The method I use in this study is to perform normative and empirical legal research. Where the nature of this paper is descriptive. The author uses primary data, secondary data and tertiary data to complement those of the authors. Then from the existing data in the end the authors analyzed the data qualitatively. The conclusions of this study is the first reversal of the burden of proof is the right of receiving gratification as the core offenses in the formulation of article 12 paragraph B (1) of Law 20/2001 included the element